Natural Remedies for the Treatment of Beta-Thalassemia and Sickle Cell Anemia—Current Status and Perspectives in Fetal Hemoglobin Reactivation. (2nd October 2014) - Ng, Noel Yat Hey; Ko, Chun Hay
Abstract : For the treatment of β -thalassemia and sickle cell disease (SCD), pharmacological induction of fetal hemoglobin (HbF) production may be a promising approach. To date, numerous studies have been done on identifying the novel HbF-inducing agents and understanding the underlying mechanism for stimulating the HbF production. In this review, we have summarized the identified HbF-inducing agents by far. By examining the action mechanisms of the HbF-inducing agents, various studies have suggested that despite the ability of stimulating HbF production, the chemotherapeutic agents could not be practically applied for treating β -hemoglobinopathies, especially β -thalassemia, due to the their cytotoxicity and growth-inhibitory effect. Owing to this therapeutic obstacle, much effort has been put on identifying new HbF-inducing agents from the natural world with the combination of efficacy, safety, and ease of use. Therefore, this review aims to (i) reveal the novel screening platforms for identifying potential inducers with high efficiency and accuracy and to (ii) summarize the new identified natural remedies for stimulating HbF production. Hopefully, this review can provide a new insight into the current status and future perspectives in fetal hemoglobin reactivation for treating β -thalassaemia and SCD.